2018
DOI: 10.3389/fchem.2018.00336
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Polyoxometalates Against Moraxella catarrhalis

Abstract: The antibacterial activity of 29 different polyoxometalates (POMs) against Moraxella catarrhalis was investigated by determination of the minimum inhibitory concentration (MIC). The Preyssler type polyoxotungstate (POT) [NaP5W30O110]14− demonstrates the highest activity against M. catarrhalis (MIC = 1 μg/ml) among all tested POMs. Moreover, we show that the Dawson type based anions, [P2W18O62]6−, [(P2O7)Mo18O54]4−, [As2Mo18O62]6−, [H3P2W15V3O62]6−, and [AsW18O60]7− are selective on M. catarrhalis (MIC range of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
35
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 58 publications
3
35
0
1
Order By: Relevance
“…In contrast, it has been evidenced that gold nanoparticles (AuNPs) are non-toxic, [7][8][9] and in the last decade conjugates of AuNPs with antibiotics [10][11][12][13][14] or other antibacterial agents [15][16][17][18][19] have been shown to improve antibacterial activity against biolms. Besides, several polyoxometalates (POMs), which can be seen as negatively charged molecular oxides incorporating metals (mainly tungsten, molybdenum and vanadium) in high oxidation states, 20 have shown important antibacterial activity, [21][22][23][24][25][26] and notably two examples of anti-biolm POM composites have been reported in the literature. 27,28 In this context, the use of POMs as active antibacterial agents supported by AuNPs represents a promising alternative.…”
mentioning
confidence: 99%
“…In contrast, it has been evidenced that gold nanoparticles (AuNPs) are non-toxic, [7][8][9] and in the last decade conjugates of AuNPs with antibiotics [10][11][12][13][14] or other antibacterial agents [15][16][17][18][19] have been shown to improve antibacterial activity against biolms. Besides, several polyoxometalates (POMs), which can be seen as negatively charged molecular oxides incorporating metals (mainly tungsten, molybdenum and vanadium) in high oxidation states, 20 have shown important antibacterial activity, [21][22][23][24][25][26] and notably two examples of anti-biolm POM composites have been reported in the literature. 27,28 In this context, the use of POMs as active antibacterial agents supported by AuNPs represents a promising alternative.…”
mentioning
confidence: 99%
“…W 6+ , V 5+ ). Earlier studies showed that these inorganic drug candidates possess potential anti-viral, [10][11][12] -bacterial, 13,14 -protozoal, 15 -tumor, 16,17 -Alzheimer 18 and -diabetic activities. 8,9 However, their molecular modes of action are poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…90 POM activity depends on composition, shape, and size, but in the case of medium-size polyoxotungstates (POTs, charge > À12 and number of addenda atoms #22) the activity correlates with the total net charge. 91 POMs exhibiting the highest activity towards Helicobacter pylori are mostly Keggin-type POTs, polyoxovanadotungstates and large highly negatively-charged POMs, whereas in the case of Streptococcus pneumoniae, the most active POMs were ascribed to be polyoxovanadates, especially decavanadate, which was also very active against other bacteria.…”
Section: Antiviral and Antibacterial Polyoxometallatesmentioning
confidence: 99%